The relationship between being in places intended for the use of narcotic drugs and psychotropic substances – A descriptive and analytical study - Hakami, Hafiz Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
The presence in places intended for the use of drugs, and psychotropic substances is closely related, as the criminal incident of being in places intended for drug abuse, and psychotropic substances is the same, and the researcher aims in his study to clarify the rules, and legal provisions related to the presence in places intended for drug abuse, and psychotropic substances by following the descriptive analytical approach, and the researcher has reached in this study to several results, and recommendations, where the most prominent results of the research are as follows:Being in places of drug use and psychotropic substances is considered ccriminalised to prevent leading to use and trade. The relationship between using drugs and psychotropic substances in terms of being in these places is a common relationship from the perspective of the legal characterisation or the criminal liability for being in these places .As far as the researcher has been able to determine, there is no legal text that differentiates between using and abusing in the provisions related to drugs and psychotropic substances.There is a criminal liability for being in places of using drugs and psychotropic substances as the physical and mental elements exist for the crime of being in those places.The prescribed penalty for being in places of using drugs and psychotropic substances is part of the lenient penalties that are provided for by most laws as the offence leads to use and trade.Consideration of excluding some groups from the provision of being in places of using drugs and psychotropic substances for they are closely-related to those who provide such places. The most prominent recommendations were as follows: Organising seminars and conferences and conducting research to elucidate how dangerous being in places of using drugs and psychotropic substances is.Raising society’s awareness, especially the young age groups, regarding being in suspicious places. Reviewing laws in terms of distinguishing between using drugs and using psychotropic substances from the perspective of significance and effect.Conducting comparative studies related to the present study’s topic and publishing them on a broad scale for more knowledge enrichment. Follow the judicial rulings related to the presence in places of use of drugs and psychotropic substances.
Keywords: drugs; psychotropic substances; elements of crime; criminal liability; motive